NILAI EKONOMIS PEMANFAATAN ONGGOK SEBAGAI PAKAN OLAHAN ALTERNATIF TERNAK BEBEK DI METRO LAMPUNG - Yateno Yateno; Widya Sartika Sulistiani (SINAR SANG SURYA, 2017)
Tapioca waste is a solid waste tapioca starch factory which still has nutritional content and can be used as raw material of alternative duck livestock feed. Analysis of the nutritional value of protein, fat, fiber and carbohydrates has been done on raw materials before and after fermentation. Observing the growth of ducks after being fed fermented feeds. Economic review of duck farming using alternative feed from fermentation process of onggok as processed feed for duck livestock. The purpose of this community service is to make operational cost efficiency or production cost of livestock and increase farmer's income. The method used by approach comparing standard costing of operational cost or production cost which is commonly issued by breeder with operational cost or production cost with alternative processed feed from fermentation process of duck for duck livestock. The result of research can reduce cost (reduce cost) operational or production cost equal to 37,11%, so it will be directly proportional to farmer income that is income will increase.